Development of the Russian socio-economic system: challenges and prospects - Alekseenko M. V., Golub I. I., Verenikina A. O., Terioshina V. V., Medvedeva N. V., Shpak A. S., Krutova O. V., Kashirin A. I., Poletaev I. V., Kruglov V. N., Tiutin D. V., Kruglov V. N., Petrov A. M. (Development of the Russian socio-economic system: challenges and prospects, 2024)
this study examines the modern mechanisms and peculiarities of implementing targeted education as a tool for providing highly qualified personnel to strategically important sectors of the Russian economy. The author emphasizes the particular relevance of targeted education in the context of global challenges and technological transformations facing the country. The paper analyzes the potential of targeted education as a factor capable of significantly influencing the long-term development and competitiveness of the Russian economy, and identifies directions for further development of the targeted education system.
Keywords: студенты; молодежь; работодатели; вузы; employers; students; абитуриенты; кадровое обеспечение; universities; заказчики; Young people; целевое обучение; стратегически значимые отрасли; targeted education; staffing; strategically important industries; applicants; customers